2019
DOI: 10.22201/ib.20078706e.2019.90.2186
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use of jaguar (Panthera onca) in a tropical forest in northern Quintana Roo, Mexico

Abstract: The study was carried out in a median stature tropical forest in the north of Quintana Roo during 2008, 2010-2012, using camera traps to record activity and habitat use by jaguar and other vertebrates. Spatial and temporal variations in habitat use, activity patterns, and species associations were analyzed using a chi-squared test (x 2 ). Generalized linear models (GLM) were used to determine which variables influenced the presence of jaguars in the study area. Jaguars were most frequently recorded in acahual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…(17,18) En este sentido, se ha generado información abundante y diversa sobre los hábitos de alimentación y uso de presas del jaguar. (19,20) Así mismo, debido a que la interacción humano-jaguar es una de las principales amenazas que confrontan las poblaciones de jaguares, (13) se requiere entender cuál es la percepción y perspectivas que tienen las personas que habitan en zonas cercanas a los felinos o que incluso son afectados por el jaguar. Existen percepciones negativas generadas por el miedo a la depredación del ganado y los ataques fortuitos a personas, (21) las cuales influyen en las actitudes y el comportamiento, como la matanza de los jaguares, y que pueden afectar la aceptabilidad social, la cual además varía regionalmente.…”
Section: Introductionunclassified
“…(17,18) En este sentido, se ha generado información abundante y diversa sobre los hábitos de alimentación y uso de presas del jaguar. (19,20) Así mismo, debido a que la interacción humano-jaguar es una de las principales amenazas que confrontan las poblaciones de jaguares, (13) se requiere entender cuál es la percepción y perspectivas que tienen las personas que habitan en zonas cercanas a los felinos o que incluso son afectados por el jaguar. Existen percepciones negativas generadas por el miedo a la depredación del ganado y los ataques fortuitos a personas, (21) las cuales influyen en las actitudes y el comportamiento, como la matanza de los jaguares, y que pueden afectar la aceptabilidad social, la cual además varía regionalmente.…”
Section: Introductionunclassified
“…Human activities are kinds of economic, recreational, or illegal activities carried out by humans that directly affect jaguar presence or biological processes within jaguar range (Carvalho et al 2015;Jordan et al 2016;Jędrzejewski et al 2017;Silva et al 2018;Ávila-Nájera et al 2019;Ávila-Nájera et al 2020). For such human activities 11 metrics were identified, including level of protection, distance to protected areas, cattle density, human activities, hunting pressure, forest loss, human footprint, distance to tourism, number of dams, fires, and indigenous communities nearby (Table 3).…”
Section: Anthropogenic Variablesmentioning
confidence: 99%
“…At the core area level they preferred well developed tropical forests regardless of availability. Using photo trapping, Ávila-Nájera et al (2019) observed that jaguars in Yum Balam JCU selected old secondary growth forests over other vegetation types. In general, we observed that jaguars in the study region preferred areas with low disturbance and dense vegetation, avoiding human modified areas as in other parts of the Selva Maya (Chávez, 2010;Conde et al, 2010;Figueroa, 2013;de la Torre et al, 2017) Our results support previous observations that jaguars use forested areas in the northeastern portion of the Yucatán Peninsula, and highlight the importance of conservation of these habitats throughout the region (Figueroa, 2013;de la Torre et al, 2017;Cruz et al, 2021).…”
Section: Habitat Usementioning
confidence: 99%